Aspects of Manubura Village Weavers' Fighting Power in Facing the Digital Age: Aspek Daya Juang Penenun Desa Manubura Dalam Menghadapi Era Digital - Barus, Debi Angelina BR.; Goit, Maria Apriyani Dua; More, Rosafina Dajia; Goit, Maria Riciana Dua; Busa, Jeanne Aprilia Buu; Gewar, Salvi Yulivania; Yulyani, Theresia (Psikologia : Jurnal Psikologi, 2025)
In the current era of globalization, we are faced with changing times where everything is digital. Weavers are required to struggle to face the current digital era. This research was conducted with the aim of finding out the fighting power of weavers in facing the digital era. This type of research is descriptive qualitative with observation and interview research methods. The results of this research show that weavers' fighting power in facing the digital era is influenced by two aspects. Namely the aspect of control (control) and the aspect of origin and ownership or origin and recognition. Highlights: Adaptation to Digitalization – Weavers must adapt to digital tools to stay competitive. Control Aspect – The ability to manage resources and technology influences their success. Ownership & Recognition – Acknowledging their origins and cultural identity strengthens their resilience. Keywords: Adversity Quotient, Era Digital, Weaver